Peter Brown: The Cult of the saints. Its Rise and Function in Latin Christianity. XV y 187 pp. SCM Press Ltd. Chicago, 1981. - Fernández Hernández, G. (Gerión. Revista de Historia Antigua, 1984)
Sin resumen